Treatment-related changes in brain activation in patients with fibromyalgia syndrome - Diers, Martin; Schley, Marcus; Wang, Haili; Flor, Herta (Experimental brain research, 2012)
Little is known about the effects of successful treatment on brain function in chronic pain. This study examined changes in pain-evoked brain activation following behavioral extinction training in fibromyalgia patients. Using functional magnetic resonance imaging, brain activation to painful mechanical stimuli applied to the 2nd phalanx of the left 2nd digit (m. flexor digitorum) was assessed in 10 patients with fibromyalgia syndrome (FM) before and after behavioral extinction training. The behavioral treatment significantly reduced interference from pain in the FM patients. Mechanical pain threshold and pain tolerance increased significantly after treatment. Activation in the insula shifted bilaterally from a more anterior site before treatment to a more posterior location after treatment. The pre- to post-treatment reduction in both interference related to pain and pain severity were significantly associated with bilateral activation in pain-evoked activity in the posterior insula, the ipsilateral caudate nucleus/striatum, the contralateral lenticular nucleus, the left thalamus and the primary somatosensory cortex contralateral to the stimulated side. These data show a relation between successful behavioral treatment and higher activation bilaterally in the posterior insula and in the contralateral primary somatosensory cortex. Future studies should compare responders and non-responders for differential treatment effects and examine in more detail the mechanisms underlying these changes.
Gesehen am 25.04.2018